From Monodisciplinary via Multidisciplinary to an Interdisciplinary Approach Investigating Air-Sea Interactions – a SOLAS Initiative. Issue 4 (3rd July 2020) - Marandino, Christa; van Doorn, Erik; McDonald, Natasha; Johnson, Martin; Açma, Bülent; Brévière, Emilie; Campen, Hanna; Carou, Silvina; Cocco, Emilio; Endres, Sonja; Hilmi, Nathalie; Hopkins, Frances; et al.
Abstract: Understanding the physical and biogeochemical interactions and feedbacks between the ocean and atmosphere is a vital component of environmental and Earth system research. The ability to predict and respond to future environmental change relies on a detailed understanding of these processes. The Surface Ocean-Lower Atmosphere Study (SOLAS) is an international research platform that focuses on the study of ocean-atmosphere interactions, for which Future Earth is a sponsor. SOLAS instigated a collaborative initiative process to connect efforts in the natural and social sciences related to these processes, as a contribution to the emerging Future Earth Ocean Knowledge-Action Network (Ocean KAN). This is imperative because many of the recent changes in the Earth system are anthropogenic. An understanding of adaptation and counteracting measures requires an alliance of scientists from both domains to bridge the gap between science and policy. To this end, three SOLAS research areas were targeted for a case study to determine a more effective method of interdisciplinary research: valuing carbon and the ocean's role; air-sea interactions, policy and stewardship; and, air-sea interactions and the shipping industry.